Pattern of Dermatological Disease and its Relation to Gender in Lumbini Medical College Teaching Hospital - Shrestha, Pratistha; Mikrani, Jameel Akhthar (Journal of Lumbini Medical College, 2016)
Introduction: The pattern of skin disease differs in different countries, and within various region of a country depending on socio-economic, racial and environmental factors. Many researchers have reported various patterns of skin disease in different countries. This type of study has not been done in this part of country. So, we decided to study, assess and compare the different pattern of dermatological disease in patients visiting our centre. Methods: This was retrospective study done from the hospital record of Lumbini Medical College Teaching Hospital (LMCTH). The study was carried out from September 2014 to December 2014 while the data were accessed from the records of respondents from September 2013 to August 2014. The diagnosis was categorized into 10 groups. The diagnosis which did not fit any category was kept in “Others”. The 10 categories include acne, bacterial infection, dermatophytes, eczema, leprosy, pigmentory diseases, psoriasis, scabies, urticaria and viral infection. Data was collected based on gender and categorized according to the diagnosis. Microsoft Excel was used for data entry while all the analysis both descriptive and inferential statistics was done using SPSS version 21. Results: There were a total of 7967 patients visiting Dermatology OPD. Out of the total patient, there were 52.10% female and 47.89% male and this difference was statistically significant. In both gender eczema was the most common skin disease. Eczema was significantly more common in male whereas acne was significantly common in female. Most of the patients were from age group of 15-30 yrs with eczema being commonest in this age group. Conclusion: Eczema and dermatophytes are the most common dermatological diseases. Eczema is significantly more common in male. Acne is significantly more common in female. DOI: https://doi.org/10.22502/jlmc.v3i1.63